Cost and Outcome in Pediatric Ischemic Stroke. (October 2015) - Hamilton, William; Huang, Haijuan; Seiber, Eric; Lo, Warren
The cost of childhood stroke receives little notice. The authors examined potential drivers of cost and outcome to test whether (1) neonatal strokes cost less than childhood strokes, (2) associated diseases influence cost, (3) arterial ischemic stroke is more costly than sinovenous thrombosis, and (4) cost correlates with outcome. The authors reviewed records of 111 children who sustained arterial ischemic stroke or sinovenous thrombosis between 2005 and 2010 to identify costs for the following year. They assessed outcomes in 46 with the Recovery and Recurrence Questionnaire and the Pediatric Quality of Life Inventory. Neonatal strokes cost less than childhood stroke. Strokes associated with congenital heart disease or vasculopathy cost the most, while perinatal or idiopathic strokes cost the least. Higher costs are correlated with worse impairment and poorer quality of life. Stroke etiology significantly influences the cost of pediatric stroke. Future cost–benefit studies must consider etiology when estimating the incremental costs associated with stroke.